Transinusal Pathway Removal of an Impacted Third Molar with an Unusual Approach: A Case Report and a Systematic Review of the Literature - Luan Mavriqi; Felice Lorusso; Gianluca Tartaglia; Francesco Inchingolo; Antonio Scarano (MDPI AG, 2022)
Background: The purpose of the present case report was to investigate a very rare ectopic third molar removal by a trans-sinusal approach and report the study findings through a systematic review of the literature on this topic. Case presentation: A 38-year-old female patient was visited for pain at the level of the right maxillary region. No relevant medical history was reported. The CBCT tomography assessment revealed an impacted third tooth at the level of the postero-lateral maxilla. Review Methods: An electronic search was performed through Boolean indicators query on Pubmed/Medline, EMBASE, Cochrane Library databases. The clinical reports were identified and selected in order to perform a descriptive analysis. The surgical approach concerned a trans-sinusal access to the site for the ectopic tooth removal with a lateral antrostomy. No evident inflammatory alteration was associated to the ectopic tooth and a non-relevant post-operative sequelae was reported at the follow up. Results: A total of 34 scientific papers were retrieved from the database search. Only two cases reported a wait-and-see radiographical follow-up approach, while the most common treatment was surgical removal, also for asymptomatic cases. Conclusion: The third-molar ectopic tooth into the maxillary sinus is an uncommon occurrence that is beast treated by an in-chair intraoral tran-sinusal approach, with a consistent reduction of the invasivity, a mild morbidity and a successful functional outcome.